2020
DOI: 10.3389/fendo.2020.568446
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Footprints of the Immune Assault on Pancreatic Beta Cells in Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is a chronic disease caused by the selective destruction of the insulin-producing pancreatic beta cells by infiltrating immune cells. We presently evaluated the transcriptomic signature observed in beta cells in early T1D and compared it with the signatures observed following in vitro exposure of human islets to inflammatory or metabolic stresses, with the aim of identifying "footprints" of the immune assault in the target beta cells. We detected similarities between the beta cell signatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 103 publications
(166 reference statements)
4
18
0
Order By: Relevance
“…1, E and F). These pathways, including "type 1 diabetes mellitus," were in general similar to previous observations made in  cells obtained from patients affected by T1D, from adult human islets, or from EndoC-H1 cells exposed to IFN (9,27,28). Among the downregulated pathways (Fig.…”
Section: Scrna-seq Of Ifn-treated Ipsc-derived Islet-like Cells Show...supporting
confidence: 87%
“…1, E and F). These pathways, including "type 1 diabetes mellitus," were in general similar to previous observations made in  cells obtained from patients affected by T1D, from adult human islets, or from EndoC-H1 cells exposed to IFN (9,27,28). Among the downregulated pathways (Fig.…”
Section: Scrna-seq Of Ifn-treated Ipsc-derived Islet-like Cells Show...supporting
confidence: 87%
“…Subsequent changes in b cells induces their senescence and further increases intra-islet immune cells infiltration. Studying the molecular footprint of stressed b cells allows to characterize the stressor (10). The link between stressed b cell and the induction of T1D is evident under the action of toxins such as alloxan or streptozotocin (138).…”
Section: Role Of B Cellsmentioning
confidence: 99%
“…Transcriptomic studies after in vitro stimulation of b cells from recent-onset and long-standing T1D showed early activation of pattern recognition receptors (PRR), upregulation of major histocompatibility complex (MHC) class I expression. In a later phase, T-cell activation and recruitment profiles and upregulation of cytokines and immune check point molecules are observed (10). The recognition of host nucleic acids by TLR 3, 8 or 9, retinoic acid inducible gene (RIG-1) or melanoma differentiation-associated protein 5 (MDA-5) leads to transcriptional expression of inflammatory mediators to eliminate pathogens, but also activate an autoimmune response, as a side effect.…”
Section: Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR3 expression in T cells has been identified in inflamed pancreata and pancreatic draining lymph nodes from donors with T1D ( 9 , 10 ) along with islet β-cell expression of monocyte chemoattractant protein-1 [MCP-1 ( 11 )]. Further potential contributors to a chemoattractive/pro-inflammatory environment are the expression of IFN-α ( 12 ), and later in disease progression, IL-1β ( 13 ), the latter potentially secreted by virally infected β cells or by α cells ( 14 ). In addition, the scene in the islets appears altered with increased HLA Class I (HLA-I) expression in both α and β cells ( 15 ) and changes in the extracellular matrix ( 16 ) (among others) that can be interpreted as signs of a confrontation.…”
Section: Investigating the Scene Of The Crime: Evidence Of Criminal Action Within Islets In T1dmentioning
confidence: 99%